Phenolic resin derived from Jatropha curcas seed-husk lignin as phenol substitute (UNED Research Journal, 2015)
Phenolic resin derived from Jatropha curcas seed-husk lignin as phenol substitute. A phenolic resin was made, with a fraction of the phenol content substituted by lignin extracted from Jatropha curcas seed husk. The husk was analysed for chemical composition, finding a high quantity of lignin (47% mass fraction). This lignin was extracted using an alkaline pulping method, followed by precipitation with acid. Several lignin-modified phenolic resins were made, using different lignin contents, in mixtures with formaldehyde in alkaline conditions, and curing at 65 ºC for 6 hours. It was noticed that the lignin substitution percentage affects the resin’s mechanical properties, obtaining better results with a 50% substitution. These resins showed good thermal behaviour, electrical insulation properties and good physical stability against water, acidic solutions and organic solvents, but it lacked on stability against alkaline solutions. It is concluded that there is a good opportunity for using the J. curcas seed husk lignin as partial substitute of phenol in phenolic resins, without sacrificing their physicochemical properties. There is a wide range of possibilities on using J. curcas agro-industrial residues as a renewable feedstock.
Keywords: Jatropha curcas; lignin; phenolic resin; lignin-formaldehyde resin; physicochemical properties.